2019
DOI: 10.1108/jic-02-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enterprise social networks use on exploitative and exploratory innovations

Abstract: Purpose The purpose of this paper is to investigate the links between the enterprise social networks (ESN) use and the exploitative and exploratory innovations and deepen the analysis by examining the mediating role of the sub-dimensions of intellectual capital (IC) in these relationships. Design/methodology/approach The authors use a quantitative method based on the questionnaire administrated to a sample of 248 middle managers working in Tunisian ICT firms. Regarding the data analysis, the authors use a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(102 citation statements)
references
References 75 publications
5
96
0
1
Order By: Relevance
“…+ MVE = Stock price at the end of April after financial year-end of company (Deswanto & Siregar, 2018) multiplied with outstanding shares (market capitalization) (Loh et al, 2017;Xu et al, 2007) D = Book value of total debts (current liabilities + long-term liabilities) TA = Book value of total assets This research also control for other variables: 1) Age, the longer the companies sampled have been established, it has the more time to convert HC to SC (Nimtrakoon, 2015;Berraies, 2019). 2) Leverage is measured by the ratio of total debts to total assets (Altaf & Ahmad, 2019;Ginesti et al, 2018;Sardo & Serrasqueiro, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…+ MVE = Stock price at the end of April after financial year-end of company (Deswanto & Siregar, 2018) multiplied with outstanding shares (market capitalization) (Loh et al, 2017;Xu et al, 2007) D = Book value of total debts (current liabilities + long-term liabilities) TA = Book value of total assets This research also control for other variables: 1) Age, the longer the companies sampled have been established, it has the more time to convert HC to SC (Nimtrakoon, 2015;Berraies, 2019). 2) Leverage is measured by the ratio of total debts to total assets (Altaf & Ahmad, 2019;Ginesti et al, 2018;Sardo & Serrasqueiro, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…From the perspective of open innovation theory, companies can benefit from internal and external collaboration (social media, internal blogs and Web 2.0/3.0). The research reported in [84] shows the results of a quantitative study conducted within a sample of ICT companies located in Tunisia through informal interviews via Linkedin with various executives of Tunisian companies. The results underline the importance of the use of social media in the promotion of innovation actions and in the creation and strengthening of interactions and links among users.…”
Section: Social Media and Firmsmentioning
confidence: 99%
“…Indeed, few works systematically exploit those kinds of analyses [58,81,91,97]. • A positive note is represented by the fact that a number of research works include at least a basic intuitive evaluation of the users' motivations and the integration costs, which may drive the concrete adoption of the designed solution [61,62,81,84,97,106].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ICT and digital technologies represent a driving force that, so far, was transforming the way through which organizations create, develop, and use their knowledge or intellectual assets for growth (Ramadan et 2019) stated that digital technologies are a key determinant of intellectual property. Furthermore, according to Berraies (2019), digital technologies can improve the way through which employees do their tasks. Hence, digital technologies may increase the autonomy, engagement and creativity of employees (Cai et al, 2020;Flores et al, 2020).…”
Section: Literature Backgroundmentioning
confidence: 99%